2023
DOI: 10.1088/1755-1315/1247/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Indices for Spatio-Temporal Analysis of the Quality of Can Gio Mangrove for Biodiversity and Conservation

T P C Nguyen,
T H Le,
T O Nguyen
et al.

Abstract: Mangrove forest has an important role in protection against coastal erosion and carbon dioxide sequestration for climate change mitigation. The natural increase in vegetation quality can explain the increase in its health and biodiversity. This study aimed to examine the health of Can Gio Mangrove vegetation to determine its potential for preventing coastal erosion and maintaining biosphere’s conservation function. Algorithms in GIS and remote sensing were used along with the time-series temporal Landsat image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The study categorized NDVI values accordingly: values below 0 indicated bare land, while those between 0 and 0.2 represented low land cover. Ranges of 0.2 to 0.3 indicated shrub and grassland, and higher values, specifically between 0.4 and 0.9, signified dense vegetation coverage [17].…”
Section: Defining the Suitable Threshold Of Ndvi Values Representing ...mentioning
confidence: 99%
“…The study categorized NDVI values accordingly: values below 0 indicated bare land, while those between 0 and 0.2 represented low land cover. Ranges of 0.2 to 0.3 indicated shrub and grassland, and higher values, specifically between 0.4 and 0.9, signified dense vegetation coverage [17].…”
Section: Defining the Suitable Threshold Of Ndvi Values Representing ...mentioning
confidence: 99%